Identification of sea breeze front (SBF) characteristics in the dry season using doppler weather radar on the west coast area of south Sulawesi - Handayani, Nelly; Rejeki, Hasti Amrih (Journal of Physics: Theories and Applications, 2023)
Sea Breeze Front (SBF) is one of the important components of sea breeze circulation, which plays role in coastal area’s atmospheric dynamics. SBF causes significant changes in temperature and humidity profiles and initiates updrafts that induce convective activity. This study aims to determine the characteristics of SBF and its impact on convection activity using Doppler weather radar on the west coast area of South Sulawesi during dry season. SBF identification utilized PPI and CMAX products to detect convective clouds and SRI to estimate rainfall intensity, then verified it using Automatic Weather Station (AWS) and Automatic Rain Gauge (ARG). SBF was generally detected at 10.30–14.30 LT with an average moving speed of 2.04 m/s. The length of SBF ranges from 15.47–21.08 km and moves inland as far as 12.57–26.09 km with 0.51–0.89 km of column depth. There was a difference in the average value of solar radiation intensity up to 106 W/m2 and 0.5°C of temperature during SBF Days. SBF caused 17 events of convective activity with a maximum reflectivity value of 42–60 dBz and 4–8 km of cloud diameter. Five out of 17 convective activities indicated the occurrence of light rain on the surface.